Російсько-Тульський загін Армії УНР: формування та бойовий шлях (квітень – травень 1919 р.) - Ковальчук, М. (Український історичний журнал, 2018)
На підставі документальних матеріалів і спогадів сучасників розглянуто історію одного з формувань Армії Української Народної Республіки, причини його появи в національних збройних силах у квітні 1919 р, з’ясовано організаційну
структуру, основні етапи бойового шляху. Проаналізовано вплив присутності
Російсько-Тульського загону на прийняття стратегічних рішень українським
військовим командуванням, докладно реконструйовано його роль під час боїв
за Новоград-Волинський, розглянуто обставини залишення туляками української військової служби у травні 1919 р. On the basing of documental sources and memories author researches history of
Russian-Tula Detachment in the Army of Ukrainian People’s Republic in 1919. The
article scrutinizes the reasons for this military formation’s appearance in the Ukrainian
armed forces in April 1919, researches it’s operational structure, enlightens the main
phases of combat activity of the Russian-Tula Detachment during it’s sojourn in the
UPR Army. Author analyses the influence in the Ukrainian military strategy provided
by the presence of this military formation, reconstitutes in details the role of it’s soldiers
in the combat actions near Novohrad-Volynskyi, scrutinizes the circumstances of
abandonment Ukrainian army by Russian-Tula Detachment in May 1919.